PENGARUH MOTIVASI KERJA, KEPUASAN KERJA DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA BADAN KEPEGAWAIAN DAERAH BALAIKOTA SEMARANG (JL.PEMUDA NO 48 SEMARANG) - Findy Permatasari Hendayana, 13.05.51.0204 (Students Journal of Economic and Management, 2017)
This study aims to analyze the effect of work motivation, job satisfaction and work discipline on employee performance. The sample in this research is some employees of BKD Semarang city, amounting to 53 employees. Methods of data analysis using linear regression. The test results obtained that There is a positive and significant effect of work motivation on employee performance, There is a positive influence and significant job satisfaction on employee performance, There is a positive influence and significant work discipline on employee performance. Keywords: work motivation, job satisfaction, work discipline and employee performance